2016
DOI: 10.1111/bju.13518
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in immuno‐oncology and its application to urological cancers

Abstract: Recent advances in immuno-oncology have the potential to transform the practice of medical oncology. Antibodies directed against negative regulators of T-cell function (checkpoint inhibitors), engineered cell therapies and innate immune stimulators, such as oncolytic viruses, are effective in a wide range of cancers. Immune'based therapies have had a clinically meaningful impact on the treatment of advanced melanoma, and the lessons regarding use of single agents and combinations in melanoma may be applicable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
(68 reference statements)
0
10
0
2
Order By: Relevance
“…Continuing this theme into immunology, Mataraza and Gotwals reviewed the current status of immunotherapy in urological cancers. Durable responses to immunotherapy in metastatic melanoma have revolutionised this approach to cancer therapy, but as stated, there remains a significant challenge in finding biomarkers to predict responses (some of these drugs have moderate‐to‐severe toxicity risk), as well as combined therapies to combat drug resistance.…”
Section: Biomarkers In the Bjuimentioning
confidence: 99%
See 1 more Smart Citation
“…Continuing this theme into immunology, Mataraza and Gotwals reviewed the current status of immunotherapy in urological cancers. Durable responses to immunotherapy in metastatic melanoma have revolutionised this approach to cancer therapy, but as stated, there remains a significant challenge in finding biomarkers to predict responses (some of these drugs have moderate‐to‐severe toxicity risk), as well as combined therapies to combat drug resistance.…”
Section: Biomarkers In the Bjuimentioning
confidence: 99%
“… A BMJ case report discussed around the topic of simple biomarker nomenclature and classification . A comprehensive review of urinary biomarkers for bladder cancer . A validation study of a biomarker linked to sunitinib response in metastatic clear cell renal cancer . A review of immunotherapy in urological cancers . Two companion reviews of biomarker validation in immunotherapy . …”
Section: Introduction – a Quick Study On Biomarkersmentioning
confidence: 99%
“…Patients with metastatic malignant melanoma who were treated with ipilimumab had a median survival of 11 months; however, 22% of patients survived for ≥3 years with a plateau in the survival curve and in a subset of patients up to 10 years [3]. This success has not yet been replicated in prostate cancer [4]. In a more recent clinical trial involving patients with melanoma who progressed, nivolumab showed survival benefit of 72% at 1 year as compared with 42% with dacarbazine [5].…”
Section: Introductionmentioning
confidence: 99%
“…. I urge you to start with the review article and give it a full line‐by‐line read. You may need to pull out pen and paper, and practice spelling and pronouncing a number of new compounds.…”
mentioning
confidence: 99%
“…predictive vs prognostic), and the USA Food and Drug Administration (FDA) has approved such a biomarker for nivolumab response. However, even this story line is perplexing, as drug response is not always linked to the marker, and immune cell expression may be ‘inducible and dynamic’ .…”
mentioning
confidence: 99%